Hip Abduction Pillow untuk Menurunkan Resiko Dislokasi pada Pasien Pasca Operasi Total Hip Replacement - Luluk Nafisah; Masfuri Masfuri; Liya Arista (FORIKES, 2022)
Malposition of the acetabular component is a risk factor for postoperative dislocation. This study aims to identify and review studies related to the effectiveness of the use of a hip abduction pillow in reducing the incidence of dislocation in postoperative total hip replacement patients. The sources used are several online databases, namely Scopus, ScienceDirect, and SpringerLink published from 2000-2021. With keywords “Hip Abduction Pillow”, “Leg Abductor Cushion”, “adductor pillow”, “Concave Hip Abduction”, “Post Total Hip Replacement surgery”, “dislocation post total Hip replacement”, “Hip replacement”, and total hip replacement intervention